The political trilemma of contemporary social-ecological transformation – lessons from Karl Polanyi’s The Great Transformation - Novy, Andreas (Globalizations, 2022)
This article advances Rodrik's political trilemma of the world economy by using insights from Polanyi’s The Great Transformation, which helps to grasp the interwoven dynamics of long-term transformations due to climate change and geopolitical reordering on one hand, and on the other short-term political ruptures due to countermovements. Rodrik's globalization trilemma shows the incompatibility of hyperglobalization with the need for an enlarged democratic policy space. Its nodes (globalization, nation state and democracy), however, have to be redefined to grasp contemporary dynamics of deglobalization. Based on a modified political trilemma of contemporary social-ecological transformation, I discuss and compare three visions and the resultant strategies: (1) Liberal globalism, focusing on hyperglobalization and individualism, (2) nationalistic capitalism, stressing national sovereignty and authoritarian governance, and (3) foundational economy based on planetary coexistence which combines selective economic deglobalization with a strengthening of a place-based foundational economy, and their respective social-ecological infrastructural configurations.
Keywords: Great Transformation, The (Book); Polanyi; deglobalization; foundational economy; hyperglobalization; social-ecological transformation